Photochemistry: A Stable and Efficient Hematite Photoanode in a Neutral Electrolyte for Solar Water Splitting: Towards Stability Engineering (Adv. Energy Mater. 13/2014). Issue 13 (September 2014) - Kim, Jae Young; Jang, Ji‐Wook; Youn, Duck Hyun; Magesh, Ganesan; Lee, Jae Sung
<x xml:space="preserve">Abstract</x> Surface phosphate groups facilitate solar water oxidation on the surface of iron oxide thin films, even in a neutral electrolyte. The method reported by Jae Sung Lee and co‐workers in article number 1400476 provides an effective path to the stability engineering of photoelectrodes to employ any electrolyte of choice. Such stability engineering is a critical issue in solution‐based energy devices based on hybrid materials with different stability characteristics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>